Influence of the structure and thermomechanical properties of oriented carbon plastics on their tribotechnical characteristics - Dykha, Aleksandr; Drobot, Olga; Oleksandrenko, Viktor; Pidhaichuk, Svitlana; Yaroshenko, Pavlo; Babak, Oleg (Eastern-European Journal of Enterprise Technologies, 2021)
It has been established that carbon plastics are increasingly used in various industries as structural materials. By the set of their properties, carbon plastics outperform steel, cast iron, alloys of non-ferrous metals. However, the application of these materials for parts of machine friction units is still limited due to the difficult operating conditions of modern tribosystems. This work aims to conduct a comprehensive experimental study of the tribological properties of materials in the tribosystem "carbon plastic-metal" taking into consideration their structure, as well as the mechanical-thermal characteristics. Comparative tests of the dependence of the friction coefficient on load for metal and polymeric anti-friction materials have shown a decrease in the friction coefficient for plastics by 3...4 times (textolite, carbotextolite, and carbon-fiber plastics). The influence of the filler orientation relative to the slip plane on the anti-friction properties of carbon-fiber plastics was investigated; it was found that the direction of fiber reinforcement in parallel to the friction area ensures less carbon-fiber plastic wear. A linear dependence of the wear intensity of carbon-fiber plastics, reinforced with graphite fibers, on the heat capacity and energy intensity of the mated steel surface has been established. Based on the microstructural analysis, a layered mechanism of the surface destruction of carbon-fiber plastics was established caused by the rupture of bonds between the fiber parts, taking into consideration the direction of the fibers’ location to the friction surface. The results reported here could provide practical recommendations in order to select the composition and structure of materials for the tribosystem "carbon-fiber plastic-metal" to be used in machine friction units based on the criterion of improved wear resistance